Role of RF-amid Related Peptide-3 (RFRP-3) in Inhibitory Effect of Orexin A on Reproductive Function in the Animal Model of Male Wistar Rats - Hefshejanni, Jafar Alipoor; Khazali, Homayoun (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aims The aim of the present study is to examine the orexin A (OXA) signaling can leave any impact on the hypothalamic-pituitary-gonadal (HPG) axis and this impact can be relayed through the pathway of RF amide-related peptide-3 (RFRP-3, the mammalian ortholog of the avian gonadotropin-inhibitory hormone)/G-protein coupled receptor (GPR)-147 (RFRP-3 receptor) as a novel target for controlling of HPG axis in the male rats.Materials and Methods Male rats were categorized randomly into experimental groups including control vehicle, OXA, and its antagonists’ group and went through to surgical cannulation into the third ventricle. After the intracerebroventricular injection of each solution, blood samples were collected for measurements of the LH and testosterone using radioimmunoassay method. Hypothalamus of the animals were isolated for analysis of the relative expression of Rfrp-3/Gpr-147 along with Gnrh gene by Real time-PCR. Also, in the different cohort of animal sexual behavior test was done.Results It was shown that OXA significantly decreases the mean serum level of the LH and testosterone and, at the same time, its antagonists neutralize this impact. Moreover, we demonstrated that OXA has reduced the hypothalamic gene expression of Gnrh and increased the expression of Rfrp-3 and Gpr-147 genes. While OXA antagonists neutralize this impact.Conclusions The results of this study are related to the impact of orexin on the HPG axis. It is recommended that RFRP-3/GPR-147 system as the interneural pathway relay the data of orexin to the neurons of GnRH.
Keywords: orexin; RF amide-related peptide-3; luteinizing hormone; GPR-147